2020
DOI: 10.1111/aogs.14053
|View full text |Cite
|
Sign up to set email alerts
|

The potential diagnostic yield of whole exome sequencing in pregnancies complicated by fetal ultrasound anomalies

Abstract: The aim of this retrospective cohort study was to determine the potential diagnostic yield of prenatal whole exome sequencing in fetuses with structural anomalies on expert ultrasound scans and normal chromosomal microarray results. Material and methods: In the period 2013-2016 391 pregnant women with fetal ultrasound anomalies who received normal microarray results, were referred for additional genetic counseling and opted for additional molecular testing pre-and/or postnatally. Most of the couples received o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(41 citation statements)
references
References 30 publications
0
39
2
Order By: Relevance
“…Skeletal dysplasias and dysmorphic syndromes were the largest disease categories in this series. Although specific proportions are not indicated, other large case series also show dysmorphic syndromes and skeletal dysplasias as the leading diagnostic groups 3,4,8,14,40 . Ciliopathies were the largest molecular diagnostic group seen in 15% cases in this study.…”
Section: Discussioncontrasting
confidence: 55%
“…Skeletal dysplasias and dysmorphic syndromes were the largest disease categories in this series. Although specific proportions are not indicated, other large case series also show dysmorphic syndromes and skeletal dysplasias as the leading diagnostic groups 3,4,8,14,40 . Ciliopathies were the largest molecular diagnostic group seen in 15% cases in this study.…”
Section: Discussioncontrasting
confidence: 55%
“…In relation to the diagnostic yield of individual anatomical systems involved in cases with multisystem anomalies, the highest yields were observed for craniofacial dysmorphism (47% of fetuses with this anomaly were positive on ES), central nervous system anomalies (45%) and musculoskeletal anomalies (43%), while the lowest yields were for fetal hydrops (19%) and gastrointestinal anomalies (27%) (Figure 4 and Table S1). Among the 17 selected studies, only three reported data on incidental findings 22,31,32 , resulting in a frequency ranging from 1.1% to 6.1%, while four reported on secondary findings 4,26,27,29 , with a frequency ranging from 3.9% to 21%.…”
Section: Resultsmentioning
confidence: 99%
“…Most pathogenic or likely pathogenic mutations were inherited in an autosomal recessive way (60%). This diagnostic yield might be biased due to our small sample size, as it is higher than in previous studies containing fetuses with a variety of malformations on prenatal US (8.5-19.4% 8,18,19 ) and in our previous study, excluding the neurological cases that were included in this report (17% 11 ). Our diagnostic yield is comparable with previous publications investigating pES in a selected cohort of fetuses with CNS malformations.…”
Section: Diagnostic Yieldmentioning
confidence: 70%
“…When a result of CMA could not be obtained before 22 + 0 weeks of gestation and parents considered TOP, pES was initiated simultaneously. Cases 1,2,5,8,12,16,17,and 19 were also included in our previous study. 11 We adhered to our previously formulated definition of clinical impact, 11 being;…”
Section: Patient Cohort and Data Collectionmentioning
confidence: 99%